Cardiac Mesenchymal Cells Cultured at Physiologic Oxygen Tension Have Superior Therapeutic Efficacy in Heart Failure Caused by Myocardial Infarction - Bolli, Robi A. R.; Arshia, Asma; Hassan, Syed A.; Dasari, Chandrashekhar; Nong, Yibing; Guo, Yiru; Tomlin, Alex A.; Li, Qianhong (Frontiers in Cell and Developmental Biology, 2021)
Stem/progenitor cells are usually cultured at atmospheric O2 tension (21%); however, since physiologic O2 tension in the heart is ~5%, using 21% O2 may cause oxidative stress and toxicity. Cardiac mesenchymal cells (CMCs), a newly discovered and promising type of progenitor cells, are effective in improving left ventricle (LV) function after myocardial infarction (MI). We have previously shown that, compared with 21% O2, culture at 5% O2 increased CMC proliferation, telomerase activity, telomere length, and resistance to severe hypoxia in vitro. However, it is unknown whether these beneficial effects of 5% O2 in vitro translate into greater therapeutic efficacy in vivo in the treatment of heart failure. Thus, murine CMCs were cultured at 21% or 5% O2. Mice with heart failure caused by a 60-min coronary occlusion followed by 30 days of reperfusion received vehicle, 21% or 5% O2 CMCs via echocardiography-guided intraventricular injection. After 35 days, the improvement in LV ejection fraction effected by 5% O2 CMCs was >3 times greater than that afforded by 21% O2 CMCs (5.2 vs. 1.5 units, P<0.01). Hemodynamic studies (Millar catheter) yielded similar results both for load-dependent (LV dP/dt) and load-independent (end-systolic elastance) indices. Thus, two independent approaches (echo and hemodynamics) demonstrated the therapeutic superiority of 5% O2 CMCs. Further, 5% O2 CMCs, but not 21% O2 CMCs, significantly decreased scar size, increased viable myocardium, reduced LV hypertrophy and dilatation, and limited myocardial fibrosis both in the risk and noninfarcted regions. Taken together, these results show, for the first time, that culturing CMCs at physiologic (5%) O2 tension provides superior therapeutic efficacy in promoting cardiac repair in vivo. This concept may enhance the therapeutic potential of CMCs. Further, culture at 5% O2 enables greater numbers of cells to be produced in a shorter time, thereby reducing costs and effort and limiting cell senescence. Thus, the present study has potentially vast implications for the field of cell therapy.